The Importance of Social Media Ethics in Preventing Cyber ​​Crime - Ismawati Septiningsih (SYARIAH : Jurnal Ilmu Hukum, 2023)
Social media seems to have become part of modern society's life. Information openness has implications for the ease with which we can find out about all phenomena in all corners of the world. Apart from having a positive impact, the openness of social media in this era can also have a negative impact. One of them is the potential for us to be caught in criminal sanctions related to information technology crimes if we are not wise in using social media. This article will discuss the emphasis on the importance of using social media ethics to avoid being trapped by criminal regulations in the field of information technology. The results of this research are that we need to maintain ethics in using social media, especially those related to sensitive matters related to ethnicity, race, religion and intergroup (SARA) so that we can avoid legal traps.